MASS BALANCE ANALYSIS OF GLUCOSE FROM SUGARCANE BAGASSE THROUGH ULTRASONIC ENZYMATIC HYDROLYSIS - Erwan Adi Saputro; Adithya Daffa Rabbani; Miranda Annisa Anwar; Wiliandi Saputro; Intan Suhada Azmi; Ardika Nurmawati (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2026)
This study explores the conversion of sugarcane bagasse into glucose through an enzymatic ultrasonic hydrolysis process. Initially, the bagasse undergoes delignification using 6% sodium hydroxide to remove lignin and free cellulose for further processing. The delignified bagasse is then hydrolyzed using cellulase enzyme under ultrasonic conditions. The results indicate that glucose production is influenced by factors such as raw material preparation, enzyme activity, temperature, and pH. Mass balance calculations were applied to assess the input and output of materials throughout the delignification and hydrolysis processes. The findings show that 10 grams of delignified sugarcane bagasse yielded 5.955 grams of glucose, demonstrating the potential of sugarcane bagasse as a source of bioenergy through glucose production. These results support the utilization of agricultural waste in bioethanol production and contribute to sustainable energy development.